Risk assessment of imidacloprid use in forest settings on the aquatic macroinvertebrate community. (28th July 2017) - Benton, Elizabeth P.; Grant, Jerome F.; Nichols, Rebecca J.; Webster, R. Jesse; Schwartz, John S.; Bailey, Joseph K.
Abstract: The isolated effects of a single insecticide can be difficult to assess in natural settings because of the presence of numerous pollutants in many watersheds. Imidacloprid use for suppressing hemlock woolly adelgid, Adelges tsugae (Annand) (Hemiptera: Adelgidae), in forests offers a rare opportunity to assess potential impacts on aquatic macroinvertebrates in relatively pristine landscapes. Aquatic macroinvertebrate communities were assessed in 9 streams in Great Smoky Mountains National Park (southern Appalachian Mountains, USA). The streams flow through hemlock conservation areas where imidacloprid soil drench treatments were applied for hemlock woolly adelgid suppression. Sites were located upstream and downstream of the imidacloprid treatments. Baseline species presence data (pre‐imidacloprid treatment) were available from previous sample collections at downstream sites. Downstream and upstream sites did not vary in numerous community measures. Although comparisons of paired upstream and downstream sites showed differences in diversity in 7 streams, higher diversity was found more often in downstream sites. Macroinvertebrate functional feeding groups and life habits were similar between downstream and upstream sites. Downstream and baseline stream samples were similar. While some functional feeding group and life habit species richness categories varied, variations did not indicate poorer quality downstream communities. Imidacloprid treatments applied according to US Environmental Protection Agency federal restrictions did not result in negative effects to aquatic macroinvertebrate communities, which indicates that risks of imidacloprid use in forest settings are low. Environ Toxicol Chem 2017;36:3108–3119. © 2017 SETAC